Serum Lipids and Risk of Rapid Renal Function Decline in Treated Hypertensive Adults With Normal Renal Function. (5th January 2019) - Zhang, Xianglin; Wang, Binyan; Yang, Juan; Wang, Jiancheng; Yu, Yaren; Jiang, Chongfei; Xie, Liling; Song, Yun; Zhong, Biyan; Li, Youbao; Liang, Min; Wang, Guobao; et al.
Abstract: BACKGROUND: We aim to evaluate the effect of different lipids parameters, including triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), the TG to HDL-C (TG:HDL-C) ratio, total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C), on the risk of rapid renal function decline and examine any possible effect modifiers in general hypertensive patients with normal renal function. METHODS: A total of 12, 549 hypertensive patients with estimated glomerular filtration rate (eGFR) ≥60 ml/min/1.73 m 2 in the renal sub-study of the China Stroke Primary Prevention Trial were included in the analyses. The primary outcome was rapid renal function decline, defined as an average decline in eGFR ≥ 5 ml/min/1.73 m 2 per year. RESULTS: The median treatment duration was 4.4 years. After the full adjustment for TC, TG, HDL-C, and other major covariates, a significantly higher risk of rapid renal function decline was found in participants with higher TG [≥150 vs. <150 mg/dl, 7.7% vs. 5.5%; odds ratios (OR): 1.27; 95% confidence interval (CI): 1.06–1.51], higher TG:HDL-C ratio [≥2.7 (median) vs. <2.7, 7.7% vs. 5.0%; OR: 1.39; 95% CI: 1.14–1.71), lower TC (≥200 vs. <200 mg/dl, 6.0% vs. 7.0%; OR: 0.79; 95% CI: 0.67–0.93), or lower LDL-C levels (≥130 vs. <130 mg/dl, 6.1% vs. 7.0%; OR: 0.79; 95% CI: 0.67–0.94). Moreover, the increased risk of the primary outcome associated with elevated TG was particularly evident among individuals with lower total homocysteine levels [<12.4 (median) vs. ≥ 12.4 μmol/l, P interaction = 0.036]. CONCLUSIONS: Higher TG and TG:HDL-C ratio were independent risk factors for rapid renal function decline in hypertensive adults with normal renal function.